IMPLEMENTASI PROGRAM GERAKAN LITERASI SEKOLAH PADA MATA PELAJARAN PPKN DI SMP NEGERI 36 BULUKUMBA - Syam, A. Fitria; Najamuddin, Najamuddin; Bakhtiar, Bakhtiar (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2024)
This research examines the implementation of the School Literacy Movement Program (GLS) in the Pancasila and Citizenship Education (PPKN) subjects at SMP Negeri 36 Bulukumba. The main focus of the research is identifying and analyzing the challenges and impacts that arise during the GLS implementation process, with an emphasis on aspects of resource availability, student interest, teacher understanding and alignment, and support from the school. The research method uses a qualitative approach with a case study design at SMP Negeri 36 Bulukumba. Research participants involved teachers, students and school officials related to GLS. Data was collected through in-depth interviews, observations, and analysis of documents related to curriculum and literacy activities. The research results show a number of significant challenges, including a lack of availability of resources, low student interest, and a lack of teacher understanding and alignment with the concept of literacy. Research recommendations include efforts to increase the availability of resources, develop innovative strategies to increase student interest, train and mentor teachers related to literacy concepts, and strengthen school support and understanding of the importance of GLS. It is hoped that this research will contribute new thinking in increasing the effectiveness of the School Literacy Movement Program in PPKN subjects, support the goals of character and citizenship education at SMP Negeri 36 Bulukumba, and can become a reference for developing literacy programs at the national level.